Antioxidant and phytochemical content of commercial brown rice (Ecobrown) and white rice (Jasmine, Jati Super Special and Manggo Thai) for potential cosmetic rice powder raw materials (Journal of Tropical Resources and Sustainable Science (JTRSS), 2020)
Cosmetic rice powder or “bedak sejuk'' has long being used as part of traditional skincare routine. The powdered rice extract is applied on the face, usually at night and will be rinsed off the next morning to obtain smooth and clear skin complexion. Usually, the regular rice available in one’s kitchen is used to make the cosmetic rice powder but different grades of rice (based on the price) will give different effects to the skin. This study aims to investigate and compare the bioactivities and phytochemical composition of different grades of rice available in the market. The rice sample used in this study was Ecobrown rice, Jasmine White rice, Jati Super Special Tempatan rice and Manggo Thai rice. All rice samples were extracted using distilled water by maceration process. The bioactivities; antioxidant capacity was measured using DPPH assay. Phytochemical content was determined as total phenolic and flavonoid contents (TPC and TFC). High Performance Liquid Chromatography (HPLC) was also used to determine phenolic content expressed as gallic acid equivalent (GAE). The result showed that brown rice had significantly higher antioxidants with IC50 values of 6.4 mg/mL in DPPH assay. The observed activities were corresponding with total phenolic content, where EcoBrown rice has a significantly higher amount of phenolic content (p?0.05) compared to other samples. Meanwhile, almost similar TFC was observed in all rice samples with Jati Super Special. The analysis of phenolic content was correlated with HPLC analysis, where brown rice was shown to have the highest amount of gallic acid content. In conclusion, brown rice can be considered as a better choice to produce “bedak sejuk”.
Keywords: antioxidant activity; total phenolic; total flavonoid; HPLC; cosmetic rice powder; rice grade